The application of agricultural land rating and crop models to CO2 and climate change issues in Northern regions: the Mackenzie Basin case study - Brklacich, Michael; Curran, Patrick; Brunt, Douglas (Agricultural and Food Science, 1996)
The Mackenzie Basin in northwestern Canada covers approximately 1.8 million km2 and extends from 52°N to 70°N. Much of the Basin is currently too cool and remote from markets to support a viable agricultural sector, but the southern portion of the Basin has the physical potential to support commercial agriculture. This case study employed agricultural land rating and crop models to estimate the degree to which a CO2 -induced global warming might alter the physical potential for commercial agriculture throughout the Basin. The two climate change scenarios considered in this analysis would relax the current constraints imposed by a short and cool frost-free season, but without adaptive measures, drier conditions and accelerated crop development rates were estimated to offset potential gains stemming from elevated CO2 levels and warmer temperatures. In addition to striving for a better understanding of the extent to which physical constraints on agriculture might be modified by climate change, there is a need to expand the research context and to consider the capacity of agriculture to adapt to altered climates. Mackenzien jokialue sijaitsee Kanadan luoteisosassa ja on laajuudeltaan noin 1,8 miljoonaa km2. Tällä hetkellä alue on liian viileä ja etäisyydet ovat liian pitkiä, jotta maataloutta kannattaisi harjoittaa merkittävässä määrin. Jokialueen eteläosien luonnonolot ovat kuitenkin sellaiset, että taloudellisesti kannattavalle maataloudelle on edellytyksiä. Tutkimuksessa selvitettin, miten ilmastonmuutoksesta aiheutuva maailmanlaajuisen lämpötilan nousu vaikuttaa Mackenzien jokialueen luonnonoloihin. Tutkimuksessa sovellettiin maatalousmaan luokitusta ja kasvumalleja, joiden avulla arvioitiin alueen potentiaalista maataloustuotantoa muuttuneissa olosuhteissa. Analyysissä käytetyt kaksi ilmastonmuutosta kuvaavaa skenaariota viittaavat siihen, että lämpötilan nousu lyhentää nykyisin hyvin pitkää routajaksoa. Samanaikaisesti kuitenkin kuivuus ja viljan nopeutunut kasvu vähentävät hyötyä, joka maataloustuotannolle ...